Time series models - Harvey, A. C. (Andrew C.) (Harvester Wheatsheaf, 1993)
A companion volume to "The Econometric Analysis of Time" series, this book focuses on the estimation, testing and specification of dynamic models which are not based on any behavioural theory. It covers univariate and multivariate time series and emphasizes autoregressive moving-average processes.